2020
DOI: 10.3389/fphys.2020.518876
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory Functions of Nilaparvata lugens GSK-3 in Energy and Chitin Metabolism

Abstract: Glucose metabolism is a biologically important metabolic process. Glycogen synthase kinase (GSK-3) is a key enzyme located in the middle of the sugar metabolism pathway that can regulate the energy metabolism process in the body through insulin signaling. This paper mainly explores the regulatory effect of glycogen synthase kinase on the metabolism of glycogen and trehalose in the brown planthopper (Nilaparvata lugens) by RNA interference. In this paper, microinjection of the target double-stranded GSK-3 (dsGS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 81 publications
(88 reference statements)
0
5
0
Order By: Relevance
“…The main function of PYGM and PYGB is their participation in adenosine triphosphate (ATP) production, gained from the glycogen deposits, to provide sufficient energy for biological processes in cells, such as contraction in the case of muscle. PYGL produces glucose molecules to maintain the glucose level in the bloodstream [ 5 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The main function of PYGM and PYGB is their participation in adenosine triphosphate (ATP) production, gained from the glycogen deposits, to provide sufficient energy for biological processes in cells, such as contraction in the case of muscle. PYGL produces glucose molecules to maintain the glucose level in the bloodstream [ 5 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…By silencing DcGSK3 , the D. citri molting from a fifth-instar nymph to an adult was significantly disrupted. According to Ding et al, the knockdown of GSK3 significantly affected the molting and wing formation of N. lugens [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…GSK3 can inhibit glycogen synthase in insects by phosphorylating and blocking the transmission of the insulin signaling pathway [ 19 ]. Ding et al revealed that GSK3 is a key enzyme that regulates energy and chitin metabolism in N. lugens [ 20 ]. However, the molecular mechanisms by which GSK3 regulates chitin and fatty acid metabolism in D. citri have not yet been reported.…”
Section: Introductionmentioning
confidence: 99%
“…However, in the brown planthopper ( Nilaparvata lugens ), this pattern is generally reversed ( 31 , 124 ). Downstream mechanisms could include GSK3, which is associated with wing deformities ( 125 , 126 ). Wing tissues are particularly sensitive to ILPs and variation in IIS does not affect allometry or growth in other tissues ( 121 ).…”
Section: Iis Regulation Of Adult Polyphenismsmentioning
confidence: 99%